The Analysis English Figurative Languages of Song in Ariana Grande “Thank U Next” Album - Putri Wirastuti, I Gusti Agung; Sukma Dewi, Ni Made (Journal on Studies in English Language Teaching (JOSELT), 2024)
In this study discusses figurative language. The researcher takes figurative language from Ariana Grane's “Thank U Next” album. The researcher only took some of the lyrics from the 9 songs on the album. In the lyrics of the song contains a different meaning from reality. Therefore the researcher analyzed the meanings contained in the song sung by Ariana Grande. The researcher uses a qualitative method to classify the meaning contained in the song, based on the theory from Knickerbocker and Renninger and the theory of meaning by Leech. In conclusion, the 10 songs chosen by the researcher used figurative language such as Metaphor, Personifications, Hyperbole, Symbol, and Simile.